Analisis Intensi Masyarakat Muslim di Indonesia dalam Menggunakan Bank Syariah: Integrated Model - Samiaji, Maskur Seto; Arundina, Tika (Jurnal Kebijakan Ekonomi, 2023)
This study was conducted to analyze the intentions of the Muslim community regarding to their using of the Islamic banks in Indonesia. The study was structured by an integrative approach, where the Technology Acceptance Model (TAM) and Theory of Planned Behavior (TPB) were integrated by adding the religiosity variable to see its effect on the intentions of the Muslim community in Indonesia to use Islamic banks. The variables used in this study include perceived ease of use, perception of benefits, attitude, subjective norms, control over behavior, and religiosity. The research data used is primary data collected using a questionnaire in the period of March – July 2021. The respondents consist of the Indonesian Muslim community who are also sharia bank customers with a total of 500 respondents spread across 34 provinces throughout Indonesia. Furthermore, data analysis was performed using the Partial Least Square Structural Equation Modeling (PLS-SEM) method. The results showed that perceived ease of use and perceived usefulness had a positive and significant effect on attitude. Then, attitude, subjective norms, perceived behavioral control, and religiosity have a positive and significant effect on intentions. This means that the intentions of the Muslim community in Indonesia can be influenced by the proposed research variables. The results of this study are expected to provide input to industry players and regulators to increase the growth and market share of Islamic banking.